Developing a standardized national undergraduate curriculum for future healthcare professionals on self-management support for chronic conditions. Issue 1 (2nd January 2023) - Sinclair, Dawn; Savage, Eileen; Carberry, Crea; Flaherty, Sinead; Flood, Breda; Han, Selena; Conlon Heaney, Carmel; Hussey, Pamela; Larkin, Louise; Mullaney, Carmel; O' Brien, Maria; Connolly, Deirdre
ABSTRACT: This is a report on the development of the second part of a national undergraduate interprofessional standardized curriculum in chronic disease prevention for healthcare professionals in the Republic of Ireland; National Undergraduate Curriculum for Chronic Disease Prevention and Management Part 2: Self-management Support for Chronic Conditions . The development processes involved in Part 1, Making Every Contact Count for Health Behavior Change, were described earlier. This report presents an overview of the development of a national self-management support curriculum and barriers and enablers encountered. The curriculum was developed by a National Working Group, with interprofessional representation from each of the Higher Education Institutions (HEIs) in Ireland and the national health service, i.e. the Health Service Executive (HSE). All phases of the project were overseen by a Steering Group and supported in each HEI by a local working group. The aim of the curriculum is to introduce standardized self-management support education across all undergraduate and graduate entry healthcare programmes nationally to prepare future healthcare professionals with knowledge, skills and attitudes to support individuals to self-manage their chronic conditions.